A Novel Entity of Corneal Diseases with Irregular Posterior Corneal Surfaces: Concept and Clinical Relevance. Issue 1 (November 2017) - Yamaguchi, Takefumi; Shimizu, Eisuke; Yagi-Yaguchi, Yukari; Tomida, Daisuke; Satake, Yoshiyuki; Shimazaki, Jun
Abstract : Abstract: Various corneal diseases, such as hereditary corneal dystrophies, corneal infection, and bullous keratopathy, cause corneal opacity, scarring, and edema, leading to severely decreased visual acuity and loss of vision. These diseases were regarded as corneal opacity diseases, and the decreased visual acuity was considered to be predominantly caused by corneal opacity. The influence of corneal irregular astigmatism on vision has been poorly understood to date, mainly because accurate quantification of irregular astigmatism has been technically challenging. We have performed detailed analyses of the corneal higher-order aberrations (HOAs) of the anterior and posterior surfaces and total cornea in corneal diseases, using an anterior segment imaging system combined with a ray-tracing method. Subsequently, we conducted correlation analyses between corneal HOAs and visual acuities and characterized the typical HOA patterns in the corneal diseases. Our recent studies demonstrated that corneal HOAs directly degrade visual acuity in eyes with mild-to-moderate corneal opacities, such as corneal dystrophies, corneal scarring, and bullous keratopathy. The findings also suggested that correction of corneal HOAs using rigid gas-permeable contact lenses is effective in eyes with a smooth posterior surface and useful in certain patients with corneal scarring to some extent. Our data will be useful for decision making regarding surgical interventions, based on the amount of corneal HOAs. Our results further indicate the clinical relevance of irregular astigmatism in the posterior surfaces in assessing the visual function of eyes with various corneal diseases.